First record of the genus Parasitorhabditis Fuchs, 1937 (Rhabditida, Nematoda) from Iran with notes on morphological and molecular characters of the Iranian population of P. obtusa (Fuchs, 1915) Chitwood & Chitwood, 1950 - Valizadeh, Ahmad; Goldasteh, Shila; Rafiei-Karahroodi, Zahra; Pedram, Majid (Zootaxa, 2017)
Parasitorhabditis obtusa is reported from Iran for the first time. The studied population is characterised with its morphological and molecular data. Morphological characters of the recovered population is in agreement with the currently available data of the species. In molecular phylogenetic studies using partial sequences of 28S rDNA D2/D3 fragment, the species formed a clade with two other isolates of the species with maximal Bayesian posterior probability (1.00) and maximum likelihood bootstrap values (100). The species was in association with bark samples of dead coniferous trees having galleries of bark beetles. It was also recovered from inside of the body of the Mediterranean pine beetle, Orthotomicus erosus, representing a new insect host for this nematode species.